Measuring Physical Activity Regulatory Styles and Identity Among Adults 55 Years or Older. (October 2022) - Huffman, Mary Katherine; Christ, Sharon L.; Ferraro, Kenneth F.; Klenosky, David B.; Marceau, Kristine; Amireault, Steve
Objectives. The purpose of this study was to examine the psychometric properties of modified versions of the Behavioral Regulation in Exercise Questionnaire and Exercise Identity Scale for use with adults ages ≥55 years to measure regulatory styles and identity related to physical activity.Methods. Participants [ M age = 66.29 years ( SD = 7.06)] answered an online questionnaire twice across a four-week timescale. We assessed measurement invariance and convergent and divergent validity based on relations between regulatory styles, identity, and physical activity.Results. Both measures were invariant across gender and time, and findings support the convergent and divergent validity of the scales. Notably, a two-factor model of identity representing role identity and physical activity beliefs provided the best fit, and physical activity beliefs was more strongly related to introjected regulation.Discussion. Taken together, there is evidence that these modified scales are suitable for use with adults ages ≥55 years.